Ipecac-Induced Neuromuscular Weakness - J Gordon Millichap (Pediatric Neurology Briefs)
A 15-month-old girl was admitted to the University of Maryland, Department of Pediatrics, with recurrent vomiting after two previous hospitalizations for vomiting, proximal weakness, and ataxia.